Upgrade of deep bed filtration with activated carbon dosage for compact micropollutant removal from wastewater in technical scale. (1st May 2016) - Löwenberg, Jonas; Zenker, Armin; Krahnstöver, Thérèse; Boehler, Marc; Baggenstos, Martin; Koch, Gerhard; Wintgens, Thomas
Abstract: The removal of micropollutants from drinking and wastewater by powdered activated carbon (PAC) adsorption has received considerable attention in research over the past decade with various separation options having been investigated. With Switzerland as the first country in the world having adopted a new legislation, which forces about 100 wastewater treatment plants to be upgraded for the removal of organic micropollutants from municipal wastewater, the topic has reached practical relevance. In this study, the process combination of powdered activated carbon (PAC) adsorption and deep bed filtration (DBF) for advanced municipal wastewater treatment was investigated over an extended period exceeding one year of operation in technical scale. The study aimed to determine optimum process conditions to achieve sufficient micropollutant removal in agreement with the new Swiss Water Ordinance under most economic process design. It was shown that the addition of PAC and Fe 3+ as combined coagulation and flocculation agent improved effluent water quality with respect to dissolved organic pollutants as well as total suspended solids (TSS), turbidity and PO4 –P concentration in comparison to a DBF operated without the addition of PAC and Fe 3+ . Sufficient micropollutant (MP) removal of around 80% was achieved at PAC dosages of 10 mg/L revealing that PAC retained in the filter bed maintained considerable adsorption capacity. In the investigated process combination the contact reactor serves for adsorption as well as for flocculation and allowed for small hydraulic retention times of minimum 10 min while maintaining sufficient MP removal. The flocculation of two different PAC types was shown to be fully concluded after 10–15 min, which determined the flocculation reactor size while both PAC types proved suitable for the application in combination with DBF and showed no significant differences in MP removal. Finally, the capping of PAC dosage during rain water periods, which resulted in lower dosage concentrations, was efficient in limiting PAC consumption during these events without suffering from negative effects on process performance or effluent quality. Highlights: The PAC/DBF process was demonstrated in technical scale over 1 year of operation. PAC/DBF is a compact process for micropollutant removal. PAC improves filter effluent water quality with respect to TSS, PO4 –P and DOC. Incorporation of PAC in the filter bed contributes to adsorption performance. The PAC/DBF process allows short contact times for adsorption and a small footprint.